RAMAN SPECTROSCOPIC STUDY OF VAPOR LIQUID EQUILIBRIUM OF CARBON DIOXIDE ABSORPTION IN AQUEOUS MONOETHANOLAMINE - KEE, WONG MEE (2016)
Aqueous phase characterization and thermodynamic modeling are important for designing and operating C02 removal systems, thus accurate determination of equilibrium of C02 in aqueous amine is of major interest for both technical and economic considerations. Many studies are conducted on vapor liquid equilibria based on pressure change, but quantitative analysis on the liquid phase speciation is relatively scarce. Developing a reliable method to quantify species under reaction conditions is imperative to improve thermodynamic and kinetic calculations.